School Transitions: Assessing Metasubjective and Personality-Related Learning Outcomes in Students - Ermolaeva M.V; Lubovsky D.V (Moscow State University of Psychology and Education, 2019)
The paper describes a diagnostic programme developed within the framework of continuous psychological and educational support of implementation of educational standards. The study involved 390 school students of 4th classes and 226 students of 9th classes who were tested before and after their transition to a new educational level in order to evaluate the dynamics of their learning outcomes (metasubjective as well as personality-related).The tests involved tasks with partial or inconsistent problem situations and A.M. Prikhozhan's Learning Motivation Survey. The analysis of the data showed that students of 4th and 5th classes perceive their transition from one educational level to another as a challenge of uncertainty, while for most of 10th-class students it is not so. Basing on the study outcomes the authors show that technologies of student personality development play an important role in securing the continuity of psychological and educational support of implementation of the Federal State Education Standards. The role of modern training models for teachers and educational psychologists in solving the task of continuous psychological and educational support is also analysed.